The Effect of Menstrual Hygiene Management on Girl Child School Attendance at St Marys Girls Vocational School in Kamukuzi Division, Mbarara City - Tumusiime, Vanmark; Twebaze, Richard; Barigye, Enock (East African Journal of Interdisciplinary Studies, 2024)
This study assessed the effects of menstrual hygiene management on school attendance among female adolescent students at St. Mary's Girls Vocational School in Kamukuzi Division, Mbarara City. The researchers employed systematic random sampling to select 45 respondents from Form One and Form Two, as these students were expected to have experienced their menstrual periods. The majority of the respondents were aged 13-14 years. While some girls used handkerchief cloths or hand towels as menstrual management materials, most of them used sanitary pads and disposed of them in the toilets. The researchers conducted a Pearson correlation coefficient analysis in SPSS to examine the relationship between menstrual hygiene management and school attendance. The analysis revealed a weak positive correlation coefficient of 0.210, indicating a weak relationship between menstrual hygiene management and school attendance. However, the p-value of 0.167 suggested that the results were not statistically significant. The study concluded that there is an impact of menstrual hygiene management on school absenteeism, as girls who experienced longer periods tended to miss more school days. However, the weak relationship and lack of statistical significance indicate that other factors may also contribute to school attendance among adolescent girls, and menstrual hygiene management alone may not be the sole determinant. This study provides valuable insights into the challenges faced by adolescent girls in managing menstruation and its potential impact on their school attendance. It highlights the need for comprehensive menstrual hygiene management education and support programs in schools to ensure that girls have access to appropriate materials and facilities. By addressing these challenges, schools can create a supportive environment that promotes regular attendance and educational opportunities for all female students, even during menstruation